The Effect of Digital Marketing on Marketing Performance with Competitiveness as a Mediating Variable in Food Industry SMEs - Agus Nurofik; Ernani Hadiyati; Dwi Orbaningsih; Rosidi (Politeknik APP Jakarta, 2026)
This study aims to analyze the influence of digital marketing on marketing performance with competitiveness as a mediating variable in food industry SMEs. The research population amounted to 117 food industry SMEs, with a sample of 100 respondents determined through purposive sampling techniques. Data were collected using a five-point Likert scale questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results of the study show that digital marketing has a negative and significant effect on marketing performance, but it has a positive and significant effect on competitiveness. Furthermore, competitiveness has a positive and significant effect on marketing performance, but is unable to mediate the influence of digital marketing on marketing performance. These findings indicate that digital marketing has not been managed strategically and market-oriented, so it has not been able to create value that has a direct impact on marketing performance.